Credit Risk and its Impact on Earnings of Nepalese Finance Company - Acharya, Tej Prasad (Damak Campus Journal, 2023)
This study has examined the impact of credit risk on earning performance of Nepalese finance companies. The descriptive and causal-comparative research designs have been adopted for the study. The pooled data of four finance companies out of seventeen for the period of 2074/75 to 2078/79 have been analyzed using a regression model via SPSS. Impairment charge ratio and non-performing loan ratio are independent variables whereas interest spread rate, profit margin, and return on assets are the dependent variable. The regression results revealed that there is a significant and positive relationship between interest spread rate and credit risk indicators, the non-performing loan ratio has an insignificant and negative effect on earnings performance and the impairment charge ratio has an insignificant but somewhat positive effect on the earnings performance of finance companies of Nepal. Nepalese finance companies should strictly follow the prevailing NRB Directive as well as Basel II Accord while managing credit risk and finance companies should use their effort to reduce non-performing loans.